Answer:
c) 6x - 5y = 15
Step-by-step explanation:
Slope-intercept form of a linear equation: ![y=mx+b](https://tex.z-dn.net/?f=y%3Dmx%2Bb)
(where m is the slope and b is the y-intercept)
Maria's line: ![y=-\dfrac{5}{6}x+8](https://tex.z-dn.net/?f=y%3D-%5Cdfrac%7B5%7D%7B6%7Dx%2B8)
Therefore, the slope of Maria's line is ![-\frac{5}{6}](https://tex.z-dn.net/?f=-%5Cfrac%7B5%7D%7B6%7D)
If two lines are perpendicular to each other, the product of their slopes will be -1.
Therefore, the slope of Nate's line (m) is:
![\begin{aligned}\implies m \times -\dfrac{5}{6} &=-1\\m & =\dfrac{6}{5}\end{aligned}](https://tex.z-dn.net/?f=%5Cbegin%7Baligned%7D%5Cimplies%20m%20%5Ctimes%20-%5Cdfrac%7B5%7D%7B6%7D%20%26%3D-1%5C%5Cm%20%26%20%3D%5Cdfrac%7B6%7D%7B5%7D%5Cend%7Baligned%7D)
Therefore, the linear equation of Nate's line is:
![y=\dfrac{6}{5}x+b\quad\textsf{(where b is some constant)}](https://tex.z-dn.net/?f=y%3D%5Cdfrac%7B6%7D%7B5%7Dx%2Bb%5Cquad%5Ctextsf%7B%28where%20b%20is%20some%20constant%29%7D)
Rearranging this to standard form:
![\implies y=\dfrac{6}{5}x+b](https://tex.z-dn.net/?f=%5Cimplies%20y%3D%5Cdfrac%7B6%7D%7B5%7Dx%2Bb)
![\implies 5y=6x+5b](https://tex.z-dn.net/?f=%5Cimplies%205y%3D6x%2B5b)
![\implies 6x-5y=-5b](https://tex.z-dn.net/?f=%5Cimplies%206x-5y%3D-5b)
Therefore, <u>option c</u> could be an equation for Nate's line.
Answer:
m∠T = 72°
m∠U = 54°
Step-by-step explanation:
Property of an isosceles triangle,
Opposite angles of two equal sides of an isosceles triangle are equal in measure.
By this property, in the given triangle STU,
Since, ST ≅ TU,
m∠S = m∠U = 54°
Since, sum of interior angles of a triangle is 180°
m∠T + m∠S + m∠U = 180°
m∠T + 54° + 54° = 180°
m∠T = 180° - 108°
m∠T = 72°
Answer:
![2x {}^{2} - 8 = 0](https://tex.z-dn.net/?f=2x%20%7B%7D%5E%7B2%7D%20%20-%208%20%3D%200%20)
Step-by-step explanation:
![(x-2) (2x+4) = 0\\ 2x {}^{2} + 4x - 4x - 8 = 0 \\ 2x {}^{2} - 8 = 0](https://tex.z-dn.net/?f=%28x-2%29%20%282x%2B4%29%20%20%3D%200%5C%5C%202x%20%7B%7D%5E%7B2%7D%20%20%20%2B%20%204x%20-%204x%20-%208%20%3D%200%20%5C%5C%202x%20%7B%7D%5E%7B2%7D%20%20-%208%20%3D%200)
Hope This helps you..!!!!
Answer:
we can do it by simplifying 8 to
to make both powers base two, and subtracting the exponents.
Step-by-step explanation:
We have been given the expression ![\frac{2^5}{8}=2^2](https://tex.z-dn.net/?f=%5Cfrac%7B2%5E5%7D%7B8%7D%3D2%5E2)
8 can be rewritten as ![2^3](https://tex.z-dn.net/?f=2%5E3)
Hence, the given expression becomes
![\frac{2^5}{2^3}=2^2](https://tex.z-dn.net/?f=%5Cfrac%7B2%5E5%7D%7B2%5E3%7D%3D2%5E2)
After subtracting the exponents on left hand side of the equation we get:
![2^2=2^2](https://tex.z-dn.net/?f=2%5E2%3D2%5E2)
we can do it by simplifying 8 to
to make both powers base two, and subtracting the exponents.